NUTRIENT MODELLING IN COASTAL WATERS OF IZMIT BAY, TURKEY - Engin, Guleda Onkal; Gurbulak, Ercan; Celen, Meltem; Ulu, Feride; Oncel, Mehmet Salim (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
The ECOLab module of the MIKE 3 model based on the coupling between a hydrodynamic part and an ecological part which accounts for mainly the nutrient enrichment was utilized to study nutrient cycles and their contribution to eutrophication in the Izmit Bay located in the Sea of Marmara. The water quality data, including on-site parameters, produced between November 2005 and November 2006 were used for model runs and validation. The samples were collected from 8 different points on the cross-section of the bay at different depths considering the bottom point of the sea bed in order to represent the third dimension. The ecological model used in this study allows creating 3D images/results that simulate the actual situation. The spatial distribution of state variables such as, dissolved Biological Oxygen Demand (BODd), dissolved oxygen (DO), ammonia, nitrate and nitrite, and phosphate concentrations were investigated. The processes, used as arguments in the differential equations involved in ECOLab, were advective dispersive transport, biological, chemical and physical transformation process and settling. According to the model results, the discharges of main streams have a big influence on the variation of the BOD, especially in the coastal and shallow regions. Additionally, the modelled ammonia, nitrate and phosphate concentrations were determined at the discharge points of the four main streams reaching the bay.
Keywords: Nutrient dynamics; Eutrophication; Ecological modelling; Three-dimensional modelling; Model evaluation; Izmit Bay; Environmental Sciences & Ecology